จากปฐมบุคคลสู่รัฐ: พัฒนาการแห่งอำนาจตามแนวคิดศาสนา - โทอื้น, วรเชษฐ์; (มุละชิวะ), พระมหาจิรายุทธ ปโยโค (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 2 No 3 (2025): วารสาร มมร ยศสุนทรปริทรรศน์ ปีที่ 2 ฉบับที่ 3 : กันยายน - ธันวาคม 2568, 2025)
This article aims to reflect on the concept of “power” in political science, arguing that it is not confined to state institutions, laws, or coercive instruments alone, but is deeply rooted in the spiritual, cultural, and linguistic development through which human beings construct shared meanings of good and evil, as well as the legitimacy of governance. In early societies, social coexistence relied on moral consciousness, fear of nature, sacredness, and the law of karma as mechanisms for regulating behavior. As societies became more complex, “religious authority” was institutionalized as a foundation that supported social and political power through rituals, teachings, and narratives that rendered the exercise of power acceptable as “legitimate authority,” producing consent alongside everyday self-discipline. Within the Buddhist framework, the formation of the state is explained through the notion of the “Mahasammata,” in which the state emerges from moral decline and harm inflicted upon one another. As selfishness expanded, the community collectively selected a virtuous leader to preserve social order. This reflects a Buddhist social-contract logic that prioritizes virtue over force and connects to the ideal of “Dhamma-based democracy” (dhammadhipateyya), which constrains the exercise of power through justice, compassion, and accountability toward those affected. In the modern world, where trust in the state is increasingly strained, applying principles such as the Four Bases of Success (iddhipada) and the Ten Royal Virtues (dasavidha-rajadhamma) to democratic thought can help cultivate a political culture grounded in transparency, accountability, and respect for human dignity. Nevertheless, virtue must operate alongside checks and balances, the rule of law, human rights, and an open public sphere that enables critique and scrutiny, so that legitimacy becomes a “public standard” rather than a personal attribute. Ultimately, power should be understood as an ethical responsibility and a process of cultivating the “civic spirit of the state” in order to sustain a balance among security, liberty, and justice.   Keywords: Dhammocracy, primordial individual, state, religion, power